Public policies and strategic planning in Peru - Saldaña Pacheco, Raphael Ángel (2020)
The study allowed examining the importance of public policies and strategic planning as essential tools to solve society's problems, as well as to guide the vision of the country to which it aspires. The scope of the study was descriptive and the research technique, the documentation. It is proposed that, in order to strengthen the institutional framework for strategic planning in Peru, the constitutionalization of the National Strategic Planning System is necessary, in order to strengthen the autonomy of the National Center for Strategic Planning as a fully technical governing body, independent of political oscillations.